Psychological aspects of manager (leader) and subordinate communication - Tumalavičius, Vladas; Trofimovs, Igor (Doctrina. Studia społeczno-polityczne, 2019)
The article undertakes the problems of the behaviour and prognose in the mutual manager understanding. It is based on investigations of the range of different fields: sociology, management, psychology. This interdisciplinary approach is typical for the social sciences, especially for the theory of social communication. Authors show the role of the essence of the subconscious predictable of the superior’s behaviour and subordinate, what they explain on examples of different situations. They give the pattern of different versions of expectations and they come to the conclusion about necessity of investigations of psychological aspects of manager communication during training of staff in the managements.